Creating diverse livelihoods in Lower Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAF)S East African regional program has selected six sites to test interventions that address risks related to climate change and variability. Featured here is the Lower Nyando site in Kenya and ongoing activities related to making baskets as a way to diversify livelihoods and income sources. This could help create resilience to climate change in the long term. Photos. K. Trautmann.